Predictive value of mucosal TNF-alpha transcripts in steroid-refractory Crohn's disease patients receiving intensive immunosuppressive therapy - Schmidt, Carsten; Giese, Thomas; Hermann, Eva; Zeuzem, Stefan; Meuer, Stefan; Stallmach, Andreas (Inflammatory bowel diseases, 2007)
BACKGROUND: Concentrations of proinflammatory cytokines are increased in the intestinal mucosa of patients with active Crohn's disease (CD). In a prospective study we investigated whether cytokines can predict long-term remission (>6 months) in patients with steroid-refractory CD receiving treatment with infliximab or cyclophosphamide, followed by azathioprine or methotrexate. METHODS: Cytokine transcripts were quantified using real-time polymerase chain reaction (PCR) in mucosal biopsies from 19 patients with active, steroid-refractory CD before and 8 weeks after initiation of therapy. Patients were treated with cyclophosphamide (monthly treatment of 750 mg cyclophosphamide intravenously) or infliximab (5 mg/kg body weight) and were followed until relapse of the disease. Statistical analysis was performed to identify predictive factors to discriminate between patients with or without long-term remission. RESULTS: Seventeen out of 19 patients achieved remission of the disease, two patients were nonresponders, while six out of 17 patients exhibited an early recurrence. Pretreatment TNF-alpha, IL-18, MRP-14, and IL-8 transcripts were significantly correlated with long-term remission. While several cytokines, most importantly MMP-1, determined after 8 weeks were able to predict patients achieving long-term remission, only a decrease of TNF-alpha levels after 8 weeks was predictive. Overall, statistical analysis identified lower pretreatment TNF-alpha levels as the strongest predictor of long-term remission among baseline variables. CONCLUSIONS: Quantification of mucosal TNF-alpha transcripts prior to therapy allows identification of patients achieving long-term remission upon immunosuppression with infliximab or cyclophosphamide. Real-time PCR might have considerable potential in the analysis of disease activity and subsequent clinical management of patients with immunosuppressive therapies.
Gesehen am 16.06.2021